Науково-дослідна діяльність політехнічного інституту у перші роки по закінченні Другої світової війни - Мельник, Ростислав; Melnyk, Rostyslav (Видавництво Львівської політехніки, 2020)
У статті розглянуто основні аспекти організації науково-дослідної діяльності Львівського політехнічного інституту у перші роки по закінченні Другої світової війни, висвітлено зусилля керівництва закладу, скеровані на нормативне й організаційне забезпечення цієї діяльності, вирішення кадрових та матеріально-технічних проблем, з якими зіткнувся виш у повоєнний період унаслідок німецької окупації Львова та утвердження тут згодом радянської влади. Проаналізовано успіхи, яких було досягнуто у цій сфері, та невдачі, які стояли на заваді поглибленню і розвитку науково-дослідної роботи закладу. Висвітлено напрями досліджень, які у цей період сформувалися в інституті та заклали підстави для становлення і розвитку науково-дослідних шкіл у майбутньому.

The three-year occupation of Western Ukraine and the return of Soviet authorities in 1944 determined the features of the research activities of Lviv Polytechnic University in the first years after World War II. During German invasion material and technical base of University suffered greatly. Most of University laboratories were partially or completely destroyed or taken to Germany. The personnel potential of the Lviv Polytechnic also underwent considerable losses during the German occupation. When western Ukraine was under Soviet authorities University faced new challenges. Most of University staff who were of Polish origin had to return to their historical homeland, which had a very negative impact on the scientific potential of the institution. Alongside, the Soviet authorities identified research work as one of the priorities of the university's activity. The intention to turn the institution into a powerful scientific center was confirmed by its regulation documents. For this purpose, the main efforts of the management of the university in the first years after the end of the war were directed to the normative and organizational support of the research activity of the institution, as well as to the solution of personnel and material and technical problems. The normative documents set out the goals and objectives of the University in the research sphere, as well as the procedure for organizing scientific activity in the institution and providing control over it. This article presents the aspects of Lviv Polytechnic University activity in the first years after the end ofWorld War II.
Research activities of Lviv polytechnic institute in the first years after world war II
Keywords: Львівський політехнічний інститут; науково-дослідна діяльність; радянська влада; Науково- дослідний сектор; професорсько-викладацький склад; Lviv Polytechnic University; research activity; Soviet authorities; scientific and research sector; teaching staff; 304.4; 323(477; 4)